Mice and rats differ with respect to activity-dependent slowing of conduction velocity in the saphenous peripheral nerve. (10th April 2015) - Hoffmann, T.; De Col, R.; Messlinger, K.; Reeh, P.W.; Weidner, C.
Highlights: We assessed in mice the a published criteria for C fibre differentiation into sub-classes. For this, we developed an in vivo electrophysiological technique in the mouse. The criteria for differentiation into fibres sub-classes is invalid in the mouse. Abstract: We assess in mice, the electrophysiological criteria developed in humans and rats in vivo for unmyelinated (C) fibre differentiation into sub-classes, derived from the activity-induced latency increase ("slowing") in response to electrical stimulation during 6 min at 0.25 Hz followed by 3 min at 2 Hz. Fibres are considered nociceptors if they show more than 10% slowing at 2 Hz; nociceptors are further divided into mechanosensitive ("polymodal") and mechanoinsensitive ("silent") ones according to a latency shift of less and more than 1% during the first minute at 0.25 Hz, respectively. Sympathetic postganglionics are recognised by 2–10% slowing at 2 Hz; units slowing less than 2% at 2 Hz remain uncategorised. For assessment of these criteria, we also developed a novel in vivo technique for recording of peripheral single-fibres in the mouse. We compared the theoretical slowing-rate discriminator criteria with experimental data obtained from mice in vivo/in vitro and rats in vitro . Out of 69 cutaneous mouse C-fibres in vitro and 19 in vivo, only 38 (67%) and 9 (47%) met the above 1% criterion, respectively; sympathetics were not identified. In contrast, out of 20 rats nerve fibres in vitro, 19 (95%) met this criterion. We conclude that (A) our novel electrophysiological technique is a practical method for examining mouse cutaneous single-fibres in vivo and (B) the published criterion for identifying silent nociceptors in rats and humans is not applicable in mice.